2003
DOI: 10.1677/jme.0.0300069
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression pattern of prolactin in Sparus aurata

Abstract: Using reverse transcription-polymerase chain reaction and in situ hybridization, the expression of the prolactin (PRL) gene was determined during development in gilthead sea bream (Sparus aurata) for the first time. The mRNA for PRL was detected from the second day of the larval stage onwards. This transcript was also located in the adenohypophysial cells, starting at four days post-hatching and was found to be pituitary-specific. Moreover, the possible involvement of PRL in asynchronous growth in the cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
3
3
0
Order By: Relevance
“…At this time, in S. auratus levels of hormones involved in growth, metabolism and development, i.e . growth hormone (GH) and prolactin (PRL), are very low (Herrero‐Turrión et al ., 2003 a,b ). It has been demonstrated that the number of GH cells and GH mRNA expression does not increase until 30 dph (Herrero‐Turrión et al ., 2003 b ).…”
Section: Discussionsupporting
confidence: 70%
“…At this time, in S. auratus levels of hormones involved in growth, metabolism and development, i.e . growth hormone (GH) and prolactin (PRL), are very low (Herrero‐Turrión et al ., 2003 a,b ). It has been demonstrated that the number of GH cells and GH mRNA expression does not increase until 30 dph (Herrero‐Turrión et al ., 2003 b ).…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, in the current study, GH transcripts have been detected by RT-PCR and localized using ISH, at 2 and 4 days respectively. Thus, as we also observed in the ontogenic study of PRL transcript in this species (Herrero-Turrión et al 2003a), there is a small discrepancy in the cellular localization of the GH protein and its respective transcript. This is probably due to the fact that, as already mentioned, the GH gene is transcript translated in some embryonic period, and in newly hatched larvae, the GH protein accumulates in the cytoplasm in free form or in secretion vesicles and the corresponding mRNA becomes degraded.…”
Section: Discussionsupporting
confidence: 66%
“…The distinct expression levels possibly fluctuated due to differential regulation of gene expression according to the larval stage. The differences in these levels of expression of saGH in larvae have also been observed in this species for PRL (Herrero-Turrión et al 2003a) and SL (Funkenstein et al 1997;Herrero-Turrión et al 2003b). Thus, the establishment of a negative feedback by insulin growth factor 1 (IGF-I), which mediates the action of GH and PRL Moriyama et al 2000), could vary the levels of these transcripts (Reinecke and Collet 1998).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations